The determinants of a pornography actress's career life. Issue 1 (1st January 2019) - Chou, Li-Chen; Zhang, Wan-Hao; Wang, Shinn-Shyr
Abstract: Statistics on Japanese adult video (A.V.) indicated that it is an industry that produces over 4500 videos every month and has recently provided 5.27 hundred million U.S. dollars a year. All related stories and sex toys promote the culture and trades of sex goods in Japan at home and abroad. They even affect the mass in sexual life, knowledge, chats as well as values in both good and bad ways. Nonetheless, almost no empirical analysis exists of this industry. This study investigates empirically the influences of debuting age, risky-sex movies and other related factors on the career life of Japanese A.V. actresses. By analysing data concerning the Japanese A.V. actresses whose careers commenced between 2002 and 2014, the authors found that the larger the cup size of an actress, the more likely she also serves as a model entertainer, and the longer she stays. On the contrary, an A.V. actress has to retire earlier or leave the industry because of a later starting age or the numbers of risky-sex movies she has produced.